FRUIT JUICES AS A SOURCE OF INFECTION. A REVIEW - K S, Vikraman; N P, Muralidharan; S, Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Fresh fruits are always nutritious, whether taken raw or made as a juice and consumed. Everyone has an addiction towards fresh fruit juices. But fresh fruit juice always carries a risk of having contaminants in it. These contaminants are risky when it is a pathogenic agent. The risk is greater when there is an outbreak of infection. Episodes of disease related to utilization of natural product juice have been a developing general medical issue since the mid-1990s. Because of epidemiologic examinations of episodes in which juice was entrapped, the U.S. Food and Drug Administration actualized the process and control measures to manage the creation of organic product juice. The last squeeze guideline, which got powerful in 2002, 2003, and 2004, contingent upon the size of the business, necessitates that juice tasks conform to a risk investigation basic control point (HACCP) plan. The Center for Disease Control and Prevention (CDC) gets reports of food-related episodes of ailment. We looked into natural product juice-related flare-ups of disease answered to the CDC’s Foodborne Outbreak Reporting System. From 1995 through 2005, 21 juice-related flare-ups were accounted for to CDC; 10 ensnared squeezed apple or juice, 8 were connected to squeezed orange, and 3 included different sorts of organic product juice. These episodes caused 1,366 diseases, with a median of 21 cases for each flare-up (2 to 398 cases). Among the 13 flare-ups of known etiology, 5 were brought about by Salmonella, 5 by Escherichia coli O157:H7, 2 by Cryptosporidium, and one by Shiga poison delivering E. coli O111 and Cryptosporidium. Less squeeze-related flare-ups have been accounted for since the juice HACCP guideline was actualized. Some juice tasks that are excluded from handling prerequisites or don’t conform to the guidelines keep on being involved in flare-ups of sickness.